Al-5Er-Ti Master Alloy with Both Grain Refinement and Microalloying Effects - Jingrui Ma; Zhiguo Lei; Shengping Wen; Guang Yang; Wu Wei; Hui Huang; Zuoren Nie (Metals)
The phase structure, grain refinement, and microalloying effect of the Al-5Er-Ti master alloy were analyzed by a refining experiment, microhardness test, OM, SEM, and XRD. The results show that when the Er/Ti atomic ratio is 2.7, the refining effect of the Al-5Er-0.5Ti master alloy is significantly better than Al-5Er, which is due to the Ti2Al20Er phase. There are three crystal orientations of Ti2Al20Er and α-Al that satisfy the E2E model, among which (620)Ti2Al20Er<260>Ti2Al20Er//(111)Al<110>Al is the least mismatched one. When the Er/Ti atomic ratio is reduced to below 1.3, the Ti-containing phase of the Al-5Er-Ti master alloy is composed of Ti2Al20Er and Al3Ti. The primary phase size of the Al-5Er-1.5Ti master alloy decreases with the increase in cooling rate, and the grain refining effect improved more significantly. The optimum size of the Ti2Al20Er phase and Al3Ti phase is 6.0 μm and 9.5 μm, respectively. The grain size of pure aluminum is reduced from 14,000 μm to 300 μm by Al-5Er-1.5Ti master alloy refinement, and the refinement rate is 97.9%. Direct aging of the refined sample did not have a precipitation strengthening effect. After the solution and aging treatment, the peak aging of the refined sample was reached in 15 min, and the microhardness increased by 41%.